IBN AL-ARABI’S CONCEPTION OF THE HUMAN BEING (Scientific journal of the Fergana State University, 2026)
This article analyzes Ibn al-Arabi's views on the concepts of “human” and “perfect human”. Ibn Arabi's contribution to the notion of the "perfect human" possessing rational faith is discussed, along with the idea that this concept leads to the elevation of human potential, rational belief, responsible stewardship of the universe, and understanding of the relationship between humans, Allah, and His creations.